Pengaruh Edukasi Tentang Mitigasi Bencana Terhadap Kesiapsiagaan Masyarakat Di Kelurahan Mahawu Kota Manado - Ismawati Ismawati (FKIP, Universitas Palangka Raya, 2022)
Indonesia is the second ranked country with the most extreme disaster risk. Efforts to reduce disaster risk and the impact caused by disasters are to organize education, training and counseling to ensure that everyone is trained and aware of the importance of preparedness in dealing with disasters. The purpose of this study was to determine the effect of education on disaster mitigation on community preparedness in Mahawu Village, Manado City. The research method used in this study was quasi- experimental with a one-group pretest-posttest design. totaling 15 respondents using a random sampling technique of data collection using questionnaires, analyzed by Mc Nemar statistical test. The results of the study before being given education showed that preparedness was not good 9 (60.0%), after being given education showed good preparedness 13 (86.7%). Statistical test results obtained p value = 0.016 where p value = 0.05. So it can be concluded that there is a significant effect between education and community preparedness Mahawu. The conclusion in this study is that there is a significant influence between disaster mitigation education on community preparedness in Mahawu Village, Manado City. Suggestions This research is expected to increase the level of community preparedness and implement disaster mitigation such as diligently cleaning waterways and disposing of garbage in its place